Distribution and drivers of transparent exopolymer particles (TEP) and Coomassie stainable particles (CSP) in the ocean - Zamanillo Campos, Marina (Universidad Politécnica de Cataluña, 2019)
Memoria de tesis doctoral presentada por Marina Zamanillo Campos para obtener el título de Doctora en Ciencias del Mar por la Universitat Politècnica de Catalunya (UPC), realizada bajo la dirección del Dr. Rafel Simó Martorell del Institut de Ciències del Mar (ICM-CSIC) y la Dra. Eva Ortega-Retuerta.-- 228 pages [EN] Transparent exopolymer particles (TEP) and Coomassie stainable particles (CSP) are operationally defined as organic particles > 0.4 µm that are stainable with the dyes Alcian Blue (specific for acidic polysaccharides) and Coomassie Brilliant Blue (specific for proteins), respectively. They are ubiquitous in the ocean, where they play important roles in biogeochemical processes such as the carbon cycle and sea-air gas and particle exchanges. However, there is a lack of large-scale studies of TEP and CSP distributions in the ocean, particularly in the open ocean, as well as temporal studies following their dynamics over more than one complete seasonal cycle. In addition, it is not clear yet whether these particles represent independent particle fractions or not and which are their main drivers, with a particular lack of information on CSP. In this thesis, TEP and CSP distributions were characterized, combining the horizontal and vertical scales whenever possible, in distinct regions of the ocean: Atlantic Ocean (October-November 2014), Southern Ocean (January 2015 and January-March 2017) and the NW Mediterranean Sea (October 2015). Besides, a time series study was conducted in two coastal stations in the NW Mediterranean Sea for two complete seasonal cycles (2015-2017). In all cases, a number of physical, chemical and biological variables were determined in parallel in order to explore the main drivers of TEP and CSP distributions. TEP concentrations ranged from below detection limit to 446 µg XG eq L-1, whereas CSP concentrations ranged between 0.3 and 52.2 µg BSA eq L-1. The highest TEP concentrations were found in the edge of the Canary Coastal Upwelling, the Southwestern Atlantic Shelf and ...